Analisis Status Mutu Air Sungai Buol di Kabupaten Buol dengan Metode Indeks Pencemaran - Mariani, Mimi; Lihawa, Fitryane; Machmud, Marike (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the water quality status of the Buol River using the Pollution Index (IP) method. The location of the study area includes the Buol River, with a length of 60.3 km. There are 8 locations for sampling the Buol River water. Determining the location of river water sampling is done by the purposive sampling method. Location criteria are determined based on pollutant sources, namely agricultural waste, domestic waste, and industrial waste. Water quality parameters analyzed were temperature, TDS, TSS, pH, BOD, COD, DO, Nitrate, Nitrite, Ammonia, Chlorine, Sulfide, Phosphate, Surfactant, Fatty Oil, Phenol, and Total Coliform. The river water quality standard used is Republic of Indonesia Government Regulation Number 22 of 2021 Appendix VI. The analysis method for the water quality status of the Buol River is determined by the pollution index method. The results of the quality analysis of the Buol River on the parameters TSS, COD, Nitrite, Chlorine, Sulfide, and Phenol have exceeded the quality standards. The results of the analysis of the water quality status using the Pollution Index (IP) method obtained the Buol River water pollution index at sample point 2 was 3,94 (lightly polluted water quality status). The pollution index value at sample point 1 is 5.16 (moderately polluted). The pollution index value at sample point 3 is 5.24 (moderately polluted). The pollution index value at sample point 4 is 8.03 (moderately polluted). The pollution index value at sample point 5 is 7.36 (moderately polluted). The pollution index value at sample point 6 is 7.73 (moderately polluted). The pollution index value at sample point 7 is 7.40 (moderately polluted). The pollution index value at sample point 8 is 7.79 (moderately polluted).